Pectin Stabilized Fish Gelatin Emulsions: Physical Stability, Rheological, and Interaction Properties - Huang, Sheng; Wang, Hui; Wang, Shu; Sha, Xiaomei; Chen, Ning; Hu, Yueming; Tu, Zongcai (Frontiers in Nutrition, 2022)
Pectin, a kind of natural polysaccharides, shows attractive potential of natural stabilizer for protein emulsion, although it has insufficient emulsifying properties. In this study, pectin was utilized to improve the stability of fish gelatin (FG) fish oil emulsion, and the effect of pectin on the physical stability, rheology, interface and interaction properties of the FG emulsion was investigated. When pH < 6, the FG-pectin emulsion had better storage stability and salinity tolerance. The 1% (w/v) pectin could avoid phase separation during the freeze-thaw process. The liquid-gel transition of FG emulsions during storage was prevented and the improved emulsion stability was due to the enhanced viscosity, electrostatic interaction, and hydrophobic interaction. When pH ≥ 6, the emulsion was a non-Newtonian fluid, and stratified during long-term storage. Electrostatic interactions, hydrophobic interactions and hydrogen bonding of the FG-pectin complexes in the emulsion were all reduced. Overall, pectin improved the stability of FG emulsions through electrostatic repulsion, hydrophobic interactions, and steric hindrance, rather than increasing surface activity of the FG-pectin complex or reducing emulsion particle size.